The Philippine biofuels industry : Defining the strategic directions - Ranola, Roberto F. (Philippines : Department of Agriculture-Bureau of Agricultural Research and the University of the Philippines Los Banos (UPLB), 2015)
This book is the culmination of a series of studies on the production of biofuels from different feedstock sources. It present the development in the domestic biofuel industry and discussed=s different issues that the industry confronts today and the challenges that it may face in the coming years.
Chapter1. Introduction -- Chapter2. General Processes in Biofuels Production -- Chapter3. Recent Developments in Biofuels Production -- Chapter4. The Philippine Biofuels Market: A Situationer -- Chapter5. Viability of the Biofuel Industry and Investment Options -- Chapter6. Challenges and Constraints on Commercialization -- Chapter7. Rationalizing Government Policies for Sustainable Biofuels Production .
Includes bibliographical references.
Keywords: BIOFUELS